PENGARUH KUALITAS PRODUK, CITRA MEREK, DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SUNSCREEN NIVEA - Khoirunnisa, Shabrina; Syarief, Nobelson; Supriadi, Yudi Nur (Bussman Journal : Indonesian Journal of Business and Management, 2022)
This study aims to determine, prove, and analyze the effect of product quality, brand image, and price on purchasing decisions of Nivea sunscreen products in South Jakarta. The technique used in determining the number of samples with non-probability sampling with purposive sampling obtained a total sample of 75 respondents using sunscreen in South Jakarta. Data collection using a questionnaire through Google forms. The data analysis technique used descriptive analysis which was processed with SmartPLS 3.3.9 software. The data analysis technique in this research is descriptive and inferential data analysis. The results of this study state that: (1) there is a significant effect on product quality of 0.267 on the purchase decision of Nivea sunscreen; (2) a significant effect on brand image of 0.471 on the purchase decision of Nivea sunscreen; (3) there is no significant effect on the price of 0.249 on the decision to purchase Nivea sunscreen. The contribution of product quality, brand image, and price variables together is shown by the adjusted Rsquare value of 92.6% while the remaining 7.4% is caused by other factors outside this research model